Correction: Green sweet potato leaves increase Nrf2-mediated antioxidant activity and facilitate benzo[a]pyrene metabolism in the liver by increasing phase II detoxifying enzyme activities in rats. Issue 15 (18th July 2022) - Yang, Ray-Yu; Zongo, Abel Wend-Soo; Chen, Yu-Chen; Chiang, Meng-Tsan; Zogona, Daniel; Huang, Chun-Yin; Yao, Hsien-Tsung
Abstract : Correction for 'Green sweet potato leaves increase Nrf2-mediated antioxidant activity and facilitate benzo[ a ]pyrene metabolism in the liver by increasing phase II detoxifying enzyme activities in rats' by Ray-Yu Yang et al., Food Funct., 2022, ; https://doi.org/10.1039/d2fo01049f .